2015
DOI: 10.1016/j.bpj.2015.04.039
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Fiber Diffraction Recordings from Oriented Demembranated Chlamydomonas Flagellar Axonemes

Abstract: The high homology of its axonemal components with humans and a large repertoire of axonemal mutants make Chlamydomonas a useful model system for experiments on the structure and function of eukaryotic cilia and flagella. Using this organism, we explored the spatial arrangement of axonemal components under physiological conditions by small-angle x-ray fiber diffraction. Axonemes were oriented in physiological solution by continuous shear flow and exposed to intense and stable x rays generated in the synchrotron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…Recently, we developed a new technique for aligning flagellar axonemes in shear‐flows to observe oriented X‐ray fiber diffraction [Oiwa et al, ; Sugiyama et al, ; Toba et al, ]. Because we could align filamentous specimens in seconds and with angular deviations of <5°, we applied this technique to the X‐ray fiber diffraction analysis to identify dynamic structural changes or conversions of native microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we developed a new technique for aligning flagellar axonemes in shear‐flows to observe oriented X‐ray fiber diffraction [Oiwa et al, ; Sugiyama et al, ; Toba et al, ]. Because we could align filamentous specimens in seconds and with angular deviations of <5°, we applied this technique to the X‐ray fiber diffraction analysis to identify dynamic structural changes or conversions of native microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…Chlamydomonas reinhardtii is a biflagellar single‐cell green algae having dynein motors at its outer and inner arms of the flagella. In C. reinhardtii , a cooperative action of multiple dynein motors triggered by ATP produces propulsive force for the beating motion of its flagella [32–34] . We used a uniflagellar mutants of C. reinhardtii , which is known to undergo rotational motion [35–36] .…”
Section: Resultsmentioning
confidence: 99%
“…In C. reinhardtii, a cooperative action of multiple dynein motors triggered by ATP produces propulsive force for the beating motion of its flagella. [32][33][34] We used a uniflagellar mutants of C. reinhardtii, which is known to undergo rotational motion. [35][36] To study the effects of ATP antagonists on the behavior of C. reinhardtii, the demembranated model was prepared according to the previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…The axonemal components are arranged on DMTs as axial repeats that are multiples of the 8-nm tubulin-dimer repeat. Major axonemal components, such as the dynein arms and radial spokes, have 96-nm structural repeats that represent the fundamental functional unit (Bui et al, 2008;Toba et al, 2015). Previous studies have shown that MIPs possess such structural repeats: MIP1a and MIP1b make an array alternatingly and possess repeats with 16-nm spacing; those of MIP2a exhibit 16-and 32-nm spacing; those of MIP2b have 48-nm spacing; those of MIP3a and MIP3b have 16-nm spacing; and those of MIP4 exhibit 48-nm spacing.…”
Section: Fap85 Is a Component Of Mip1a Characteristic Of Chlamydomonasmentioning
confidence: 99%